Bakti Sosial Komunitas Outsider Lombok Pada Gempa Sulawesi Barat Dalam Kaitannya Dengan Sila Kedua Pancasila - Hadi, Ade Sopyan; Saputra, Ahmad Yudi (Panrannuangku Jurnal Pengabdian Masyarakat, 2024)
West Sulawesi Province was hit by an earthquake on January 15 2021. When the earthquake occurred, the Outsider Lombok community carried out social service activities. This activity aims to ease the burden on the affected communities. This social service is carried out by taking action directly onto the street. The results of this research were data that the stages carried out began with discussions regarding activities, fundraising actions and the stage of handing over donated funds. The supporting factor is collaboration with Aksi Cepat Tunjungan so that the distribution of funds is easier. Meanwhile, the inhibiting factor is the busyness of community members who are already working. The conclusion of this research is that this social service really helps the affected communities and can increase the sense of humanity of members of the Outsider Lombok community.